2012
DOI: 10.1007/s10461-011-0131-8
|View full text |Cite
|
Sign up to set email alerts
|

A Review of the Literature on Event-Level Substance Use and Sexual Risk Behavior Among Men Who Have Sex with Men

Abstract: In the United States, there continues to be high incidence of HIV infection among men who have sex with men (MSM), who represent 57% of new infections in 2009. While many studies report associations between non-injection substance use and sexual risk behavior among MSM, overall results are mixed. Summarizing these studies is difficult because researchers have used a variety of assessment periods for substance use and sexual behavior. We review the scientific literature on event-level measures, which assess sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
256
3
4

Year Published

2013
2013
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 302 publications
(286 citation statements)
references
References 66 publications
19
256
3
4
Order By: Relevance
“…That sexual sessions featuring binge drinking or crystal methamphetamine are more likely to include intercourse and are less likely to include condoms than sexual sessions that do not feature drugs has also been shown. 23 Thirdly, panel data from the same men at different points in time show that the same men having sex on crystal methamphetamine are more likely to have condomless anal sex than they are having sex on the drugs or without drugs. 24 Much time and energy has gone into (continues to go into) debating the associations between drugs, sex and risk.…”
Section: Locating Chemsex As Edgeworkmentioning
confidence: 99%
“…That sexual sessions featuring binge drinking or crystal methamphetamine are more likely to include intercourse and are less likely to include condoms than sexual sessions that do not feature drugs has also been shown. 23 Thirdly, panel data from the same men at different points in time show that the same men having sex on crystal methamphetamine are more likely to have condomless anal sex than they are having sex on the drugs or without drugs. 24 Much time and energy has gone into (continues to go into) debating the associations between drugs, sex and risk.…”
Section: Locating Chemsex As Edgeworkmentioning
confidence: 99%
“…[3][4][5][6][7][8][9][10][11][12][13][14][15] Two recent and substantive literature reviews describe how assessment of substance use with or without sex among MSM has been inconsistent among prior studies. 16,17 Despite these inconsistencies, several key themes were noted. Vosburgh and colleagues indicated that event-level use of methamphetamine and binge alcohol use provided the strongest causal link for acquisition of HIV among MSM.…”
Section: Introductionmentioning
confidence: 99%
“…But this explanation uncritically reproduces the cultural notion of 'disinhibition' to explain sexual risk-taking and neglects event-level and other analyses that find that people who engage in unprotected sex under the influence of drugs are just as likely to take sexual risks when they have not consumed these substances. 4,12,[70][71][72][73][74][75] Many alternative explanations for the correlation between drug use and sexual risk-taking are possible; those who engage in the consumption of illicit drugs may simply be more likely to engage in other risky practices (such as unprotected sex); and/or drug use may itself be prompted by shame around unprotected sex. As both illicit drug use and sex without condoms represent instances of sociomedical non-compliance, those who are led to breach one of these prescriptions may well be inclined to breach the other in certain circumstances, especially when such prescriptions fail to take into account the lived realities and constraints of people's everyday lives and desires.…”
Section: Sexualised Drug Usementioning
confidence: 99%